Efforts to Overcome Cyber Crime Actions in Indonesia - Hatta, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
The presence of the internet can penetrate the boundaries between countries and accelerate the spread and exchange of information throughout the world. Although there are many positive impacts of internet use, there are also negative impacts that disturb the community. One can easily become a criminal (cyber crime) only by creating blogs, accounts, applications, programs, sites in various mass media and social media to commit fraud, data theft, illegal use of credit cards, the spread of pornographic content, online gambling, online prostitution, hate speech, radicalism, terrorism and so on. To overcome crime in the virtual space, the government has issued Law No. 19 of 2016 concerning Amendments to Law No. 11 of 2008 concerning Information and Electronic Transactions. But not all internet users know and understand the substance of the law. Therefore, the government, employers, and institutions that are engaged in information and communication technology have the responsibility to socialize the law to the public to prevent crime in the virtual space.